2021
DOI: 10.3389/fnagi.2021.639529
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in Network Topology and Education Correlated With Sex Difference in Cognition During the Disease Process of Alzheimer

Abstract: Background: Alzheimer’s disease (AD) manifests differently in males and females. However, the neuro-mechanism and influence factors are still unknown.Objective: To explore sex differences in brain network topology during AD disease progression and its association with cognition and possible influencing factors.Methods: Resting-state functional magnetic resonance imaging (MRI) data and cognitive scores were collected from 82 AD patients (50 females), 56 amnestic mildly cognitive impaired patients (29 females), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 53 publications
4
13
0
Order By: Relevance
“…This result complements that of a report by the Lancet Commission [5]. However, only a few studies [51,52] have demonstrated the presence of sex differences in MCI. Better attention and calculation performance in men than in women could arise from the effect of estrogen [53] or sex-specific cognitive reserve [5].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This result complements that of a report by the Lancet Commission [5]. However, only a few studies [51,52] have demonstrated the presence of sex differences in MCI. Better attention and calculation performance in men than in women could arise from the effect of estrogen [53] or sex-specific cognitive reserve [5].…”
Section: Discussionsupporting
confidence: 87%
“…The brain atrophy rate of female patients with MCI is reportedly higher than that of male patients, with an additional decrease of 1.0-1.5% per year [56]. A possible explanation is that men may have higher resilience to MCI-related pathological damage to the brain [51] and better executive function than women; this finding is supported by cognitive reserve theory. However, this is different from the results of a previous study [57].…”
Section: Discussionmentioning
confidence: 91%
“…In a study comparing amnestic MCI and AD with healthy controls, a difference in right caudate nucleus atrophy was observed in females only. Alterations of functional connectivity in the somato-motor, dorsal, and ventral attention networks were identified in male patients (Li et al, 2021). In summary, our findings are in line with existing knowledge about AD.…”
Section: Simulation Studysupporting
confidence: 91%
“…[1][2][3] Evidence clearly indicates that there is an increased age-independent prevalence of Alzheimer's disease (AD) in women compared to men (average odds ratio is 1.6) and that it is consistent with sexual dimorphism in AD pathophysiology, spanning molecular pathways of brain proteinopathies, neurodegeneration, neuroinflammation, and large-scale high-order organization of the brain. [4][5][6][7][8][9][10][11][12] In addition, women who experience early menopause, either naturally or iatrogenic, represent the highest risk cluster within the menopause population of late-life cognitive decline and dementia. 13,14 The higher vulnerability of perimenopausal (transition phase) and early-menopause women than men has been established by large-scale neuropsychological studies, post-mortem investigations, biomarkerbased studies, data-driven multi-variate analysis, and experimental models of aging and AD.…”
Section: Introductionmentioning
confidence: 99%